Stock price manipulation: The role of intermediaries - Hammad Siddiqi (International Journal of Financial Studies, 2017)
We model a scenario in which there are three types of investors: fundamentalists, speculators, and trend-followers and an intermediary who cares about his reputation. Fundamentalists are rational investors with long horizons who are interested in the dividend stream. Speculators are rational investors who have short horizons and are interested in profiting from short-term price movements or capital gains. Trend-followers are behavioral investors who extrapolate price trends, and, consequently, are late entrants in the market. We show that an informed intermediary (broker) can manipulate demand (consequently stock price) without losing his reputation when there is information asymmetry. We also show that there is a trade-off between broker level competition for reputation and market liquidity. Broker level competition checks manipulation, but it adversely affects market liquidity.
Keywords: C72; D80; G10; G20; 330; stock price manipulation; broker manipulation; broker competition; heterogeneous investors; fundamentalists; speculators; trend-follower